Bactericidal effect of Q-switched Nd:YAG laser (1064 nm ) on Streptococcus mutans from carious teeth ,in vitro study - Anwer, Ayad G.; Markaryan, Karon W. (Iraqi Journal of Laser, 2009)
Dental caries (tooth decay) is one of the most prevalent infectious disease and although of multifactorial origin, Streptococcus mutans is considered the principal pathogen in its development (i.e. bacterial processes damage hard tooth structure (enamel, dentine and cementum), producing dental cavities (holes in the teeth). The bactericidal properties of the Nd:YAG laser has been researched analyzing its use in caries prevention and bacterial reduction. One hundred twenty five samples were collected from carious teeth and isolated bacteria were diagnosed using microscopic examination, culture, biochemical tests, and Api 20 strep system. The results of this study showed that a noticeable decrease in the viability of Streptococcus mutans were obtained using Q-switched Nd:YAG laser (1064 nm), (3 Hz) repetition frequency, (0.796 ,0.955) J/ cm2 energy density by applying (900,1260) number of pulses. It was concluded that the bactericidal effect of laser irradiation being dependent on the type of bacteria, energy density, number of pulses, and laser dose. Suggesting that the results obtained in this study may be useful in the treatment of dental plaque-related disease.